Evaluating Aboveground Biomass And Carbon Stock of Leucaena leucocephala in Bandar Jeli, Kelantan - Siti Noor Balqis Bukhari; Nur Aishah Izzati Abdullah; Mohamad Faiz Mohd Amin; Janshah Moktar; Ag Ahmad Mohd Yunus; Rosdi Koter; Dasrul Iskandar Darus; Roziela Hanim Alamjuri; Musri Ismenyah; Mohd Sukhairi Mat Rasat (UTS Publisher, 2024)
This study assesses the aboveground biomass and carbon stock of Leucaena leucocephala, a fast-growing leguminous tree species, in Bandar Jeli, Kelantan. L. leucocephala is recognised for its potential in agroforestry, soil improvement, and carbon sequestration, making it an ideal candidate for carbon stock evaluation in tropical regions. By applying non-destructive sampling techniques and allometric equations, the diameter at breast height (DBH) range of 5 to 15 cm was measured for each chosen stands in four stratified random sampling plots. The means for DBH, aboveground biomass, and carbon stock were 10.45cm, 70.682Mg/ha and 33.221MgC/ha respectively. The findings indicate significant carbon storage capacity, highlighting the ecological and economic benefits of L. leucocephala in reforestation and carbon offset initiatives. This study provides valuable insights into the potential role of L. leucocephala in local and regional carbon management strategies, offering a model for sustainable land use practices in tropical forest ecosystems.